Politics, democracy, and e-government participation and service delivery - Reddick, Christopher G.; Gale Group (Hershey, Pa. Information Science Reference, 2010)
Examines how e-government impacts politics and democracy in both developed and developing countries, discussing the participation of citizens in government service delivery.
section 1. E-participation. ch 1. The potential of e-participation in sustainable development evaluation : evidence from case studies ; ch 2. Citizens and e-government service delivery : techniques to increase citizen participation ; ch 3. E-government and citizen participation in Chile : the case of ministries websites ; ch 4. E-government and opportunities for participation : the case of the Mexican state web portals ; ch 5. A comparative analysis of local agenda 21 websites in Turkey in terms of e-participation ; ch 6. Government 2.0 in Korea : focusing on e-participation services ; ch 7. Internet use and political participation of American youth : the campaign of 2008 ; ch 8. Participatory e-planning : bridging theory and practice through improvements in technology -- section 2. E-democracy. ch 9. Perception differences of online voting between young and senior voters ; ch 10. 24-7 government, the permanent campaign, and e-democracy : Massachusetts governor Deval Patrick's interactive website ; ch 11. UK e-voting : a lost opportunity for participatory democracy ; ch 12. Deliberation, participation, and "pockets" of e-democracy ; ch 13. A review of city portals : the transformation of service provision under the democratization of the fourth phase ; ch 14. E-government and the EU : democratisation through technology? ; ch 15. Evaluating social networking in public democracy ; ch 16. Online activism and computer mediated communications -- section 3. E-governance. ch 17. Digital cities : towards connected citizens and governance ; ch 18. Explaining the global digital divide : the impact of public policy initiatives on e-government capacity and reach worldwide ; ch 19. Helping to bridge the digital divide with free software and services ; ch 20. Citizen consultation from above and below : the Australian perspective ; ch 21. E-government in Brazil : reinforcing dominant institutions or reducing citizenship? ; ch 22. "Potential" barriers to e-government implementation in developing countries ; ch 23. Ontology driven e-government ; ch 24. Virtual neighborhoods and e-government : a case study comparison.
Description based on print version record.
"Premier reference source."--Cover.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Internet in public administration; Political participation -- Technological innovations; Democratization -- Technological innovations; Electronic books